PELATIHAN EFIKASI DIRI UNTUK MENINGKATKAN MOTIVASI BERPRESTASI PADA SISWA SMA TEUKU UMAR SEMARANG (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2022)
Students are said to be successful in learning if there is a change in student behavior and learning outcomes. In learning activities, motivation is needed as a driving force for students when following the learning process. The phenomenon found that during online learning many students do not have the motivation to learn. One way that can be used to increase student learning motivation is to provide self-efficacy training. Self-efficacy training can help students Community service activities aim to increase students' learning motivation through self-efficacy training. The subjects in this PkM activity were students of class X SMA Teuku Umar Semarang, totaling 60 students. The implementation method used in this training activity is to use the lecture and training method. The activity was carried out in two sessions, the first session was given motivational material and the second session was given self-efficacy material and training to increase self-efficacy. The data analysis method used is descriptive and quantitative analysis. The results of data analysis using the testpaired sample t-test showed an increase in student understanding with a mean difference score of 1.50 Pretest and Posttest 4.07 with a T Test for mean equity of 2.567. Keywords: Self-Efficacy Training, Student Learning Motivation